Immune response mediated by Th1 / IL-17 / caspase-9 promotes evolution of periodontal disease - Sommer, M. E. L.; Dalia, R. A.; Nogueira, A. V. B. [UNESP]; Cirelli, J. A. [UNESP]; Vinolo, M. A. R.; Fachi, J. L.; Oliveira, C. A.; Andrade, T. A. M.; Mendonca, F. A. S.; Santamaria, M.; Felonato, M. (Elsevier B.V., 2019)
Introduction: Periodontitis is characterized by inflammatory mediators beyond T lymphocyte function and phenotype (Thl/Th2/Th17). The clinical diversity in periodontitis makes it difficult to characterize the immune response in patients. This study evaluated the profile of the adaptive immune response in the periodontal disease model. Methods: 72 rats (Wistar) were divided into a control group (CTL/day 0) and periodontitis (PD15/15 days and PD60/60 days). In the PD15 and PD60 groups, periodontal disease was induced by ligature with a silk thread placed in the cervical region of the upper first molar. After euthanasia, the periodontal tissue was analyzed by flow cytometry (CD4, CD8, CD25, CD44), semi-quantitative RT-PCR (T-bet, GATA-3, ROR gamma t), semi-quantitative RT-PCR and ELISA IFN-gamma, TNF-alpha, IFN-gamma, IL-4, IL-6, IL-10, IL-17) and by Western blotting (Caspase-9, PCNA). Results: The number of CD4(+) CD25(+), CD4(+) CD44(+), CD8(+) CD25(+) and CD8(+) CD44(+) cells and expression levels of T-bet and GATA-3 are increased in the PD60 group compared to PD15 and CTL. The ROR gamma-t gene transcript increased in the PD15 group in relation to PD60 and CTL. The cytokines IFN-gamma, TNF-alpha and IL-17 increased in the PD60 group in relation to PD15. The expression of Caspase-9 was higher in the PD60 group than in PD15. Conclusions: The results suggest that the evolution of gingivitis to periodontitis is related to the accumulation of activated Thl cells (IFN-gamma and TNF-alpha) associated with the presence of increased IL-17. Studies with inhibitors of these cytokines in periodontal disease may lead to therapy directed at blocking the inflammatory process in this pathology, interrupting bone loss.
Keywords: Cytokines; Immune response; Periodontitis; Lymphocytes